2012
DOI: 10.5897/ajpp12.509
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and pharmacologic properties of Ziziphus spina christi (L.) Willd.

Abstract: Ziziphus spina-christi known as Christ's Thorn Jujube, is a native plant that grows in tropical and subtropical regions especially in Middle East. Its extracts are important in drug development with pharmacological activities in the Middle East and South and East of Asia including Iran. For a long time, Z. spina-christi has been used in alternative medicine for the treatment of fever, pain, dandruff, wounds and ulcers, inflammatory conditions, asthma and to cure eye diseases. Z. spina-christi has recently been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 40 publications
2
66
0
2
Order By: Relevance
“…The growing trend toward the anti-oxidants is due to their ability to protect the body against damages caused by reactive free radicals that are produced during various disorders. The main phytochemical constituents of this plant are including phenolic, flavonoids, alkaloids and saponins (Asgarpanah and Haghighat, 2012). Abdel-Wahhab et al (2007) evaluated the anti-oxidant effect of methanolic Z. spina-christi leaf extract on the oxidative stress of aflatoxin in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing trend toward the anti-oxidants is due to their ability to protect the body against damages caused by reactive free radicals that are produced during various disorders. The main phytochemical constituents of this plant are including phenolic, flavonoids, alkaloids and saponins (Asgarpanah and Haghighat, 2012). Abdel-Wahhab et al (2007) evaluated the anti-oxidant effect of methanolic Z. spina-christi leaf extract on the oxidative stress of aflatoxin in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, its leaves are used to treat sores, pneumonia, dysentery, ulcer and as an antiseptics. The leaves contain phytosterols such as β-sitosterol, glycoside, flavonoids, saponins, tannins and lactone (Asgarpanah and Haghighat, 2012). Hydroalcoholic extract of Ziziphus spina-christi was found to be effective against scopolamine-induced anxiety in rats (Setorki, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Ziziphusspina-Christi was known to be active against wide spectrum of bacteria due to presence of betulic and cyanotic acid, three cyclopeptide alkaloids as well as four saponim glycosides and several flavonoids [15].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature revealed that a number of cyclopeptide and isoquinoline alkaloids, flavonoids, terpenoids and their glycosides have been found to occur in various amount in most Ziziphus species. The leaves of these plants contain betulinic and ceanothic acids, various flavonoids, saponins, erols tannins and triterpenes [22]. The aqeous extract of Z. spina Christi stem bark has shown significant antibacterial activity [23, 24 and 25], antifungal [26], antinociceptive effects [17], antioxidant activity [11and 27].…”
Section: Introductionmentioning
confidence: 99%